Transactions on edutainment IX - Cheok, Adrian David; Müller, Wolfgang; Liarokapis, Fotis; Pan, Zhigeng (Lecture Notes in Computer Science,, 2013)
This journal subline serves as a forum for stimulating and disseminating innovative research ideas, theories, emerging technologies, empirical investigations, state-of-the-art methods, and tools in all different genres of edutainment, such as game-based learning and serious games, interactive storytelling, virtual learning environments, VR-based education, and related fields. It covers aspects from educational and game theories, human-computer interaction, computer graphics, artificial intelligence, and systems design. This issue contains a special section on serious games with 8 outstanding contributions from the VS-Games 2011 conference; furthermore, there are 13 regular papers. These contributions clearly demonstrate the use of serious games and virtual worlds for edutainment applications and form a basis for further exploration and new ideas.